1987
DOI: 10.1038/bjc.1986.221
|View full text |Cite
|
Sign up to set email alerts
|

DNA content and prognosis of non-Hodgkin's lymphoma

Abstract: Summary Ninety cases of non-Hodgkin's lymphoma diagnosed prior to the use of modern therapeutic regimens and 88 cases treated with such chemotherapy were studied using conventional morphology and flow cytometry. DNA aneuploidy as determined by flow cytometry was more common among high grade (38%) than low grade (19%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
5
16
1
Order By: Relevance
“…The problems associated with the histological classification of NHL are well recognised (NCI Non-Hodgkin's Lymphoma Classification Project Writing Committee, 1985), and reproducible quantitative methods of tumour classification are required to confer additional prognostic information to guide the clinician in the selection of the most appropriate therapeutic approach. FCM analysis represents a method for the rapid estimation of nuclear DNA content in tumour cell populations, providing information on the potentially important tumour parameters of DNA ploidy and proliferative activity.Previous FCM studies in NHL have suggested that both tumour cell proliferation and the incidence of DNA aneuploidy increase with progression from low to high grade histology (Scarffe & Crowther, 1981;Braylan et al, 1984;Srigley et al, 1985; Christensson et al, 1986;Morgan et al, 1986;Bauer et al, 1986;Juneja et al, 1986) …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The problems associated with the histological classification of NHL are well recognised (NCI Non-Hodgkin's Lymphoma Classification Project Writing Committee, 1985), and reproducible quantitative methods of tumour classification are required to confer additional prognostic information to guide the clinician in the selection of the most appropriate therapeutic approach. FCM analysis represents a method for the rapid estimation of nuclear DNA content in tumour cell populations, providing information on the potentially important tumour parameters of DNA ploidy and proliferative activity.Previous FCM studies in NHL have suggested that both tumour cell proliferation and the incidence of DNA aneuploidy increase with progression from low to high grade histology (Scarffe & Crowther, 1981;Braylan et al, 1984;Srigley et al, 1985; Christensson et al, 1986;Morgan et al, 1986;Bauer et al, 1986;Juneja et al, 1986) …”
mentioning
confidence: 99%
“…Previous FCM studies in NHL have suggested that both tumour cell proliferation and the incidence of DNA aneuploidy increase with progression from low to high grade histology (Scarffe & Crowther, 1981;Braylan et al, 1984;Srigley et al, 1985; Christensson et al, 1986;Morgan et al, 1986;Bauer et al, 1986;Juneja et al, 1986) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most malignancies an abnormal DNA content -aneuploidy-has been found, and frequently it has been associated with an adverse prognosis: breast, urinary bladder, uterine cervix, ovary, colo-rectal and non-small cell lung tumors (12). In systemic non-Hodgkin lymphomas, there is no agreement concerning the prognostic value of FC (13)(14)(15)(16)(17). The published studies focusing on primary gastric lymphomas are scanty and also, the results concerning FC prognostic value are contradictory (11,12,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…It was in an attempt to reconcile the principal histopathological systems of classification and to recognise that there were more than two broad groupings within the non-Hodgkin's lymphomas that led to the consensus classification of the Working Formulation (The non-Hodgkin's lymphoma pathologic classification project, 1982 (Costa et al, 1981;Gerdes et al, 1984;Akerman et al, 1987). Measurement of DNA content by flow cytometry with determination of proliferation indices represents a further step in classifying NHL and predicting outcome (Diamond et al, 1982;Roos et al, 1985;Morgan et al, 1986;Williamson et al, 1987). Within particular categories, for example mixed centroblastic-centrocytic NHL, ploidy and proliferation index have shown correlation with prognosis (Griffin et al, 1988 While the majority of NHL are B cell in origin, both the immature and mature T cell diseases need to be characterised.…”
Section: Histopathological Classification and Pathological Variablesmentioning
confidence: 99%